Topological insulators and thermoelectric materials - Muechler, Lukas; Casper, Frederick; Yan, Binghai; Chadov, Stanislav; Felser, Claudia (Physica Status Solidi-Rapid Research Letters, 2013)
Topological insulators (TIs) are a new quantum state of matter which have gapless surface states inside the bulk energy gap [1-4]. Starting with the discovery of two-dimensional TIs, the HgTe-based quantum wells [5, 6], many new topological materials have been theoretically predicted and experimentally observed. Currently known TI materials can possibly be classified into two families [7], the HgTe family and the Bi2Se3 family. The signatures found in the electronic structure of a TI also cause these materials to be excellent thermoelectric materials [8-10]. On the other hand, excellent thermoelectric materials can be also topologically trivial. Here we present a short introduction to topological insulators and thermoelectrics, and give examples of compound classes where both good thermoelectric properties and topological insulators can be found. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Thermoelectric materials; Topological insulators